What can be learned about the enzyme ATPase from single-molecule studies of its subunit F1?. (16th November 2017) - Volkán-Kacso, Sándor; Marcus, Rudolph A.
Abstract: We summarize the different types of single molecule experiments on the F1 component of FO F1 -ATP Synthase and what has been learned from them. We also describe results from our recent studies on interpreting the experiments using a chemical-mechanical theory for these biological motors.